Milk oligosaccharide-driven persistence of Bifidobacterium pseudocatenulatum modulates local and systemic microbial metabolites upon synbiotic treatment in conventionally colonized mice - Jules A. Larke; Britta E. Heiss; Amy M. Ehrlich; Diana H. Taft; Helen E. Raybould; David A. Mills; Carolyn M. Slupsky (Microbiome, 2023)
Abstract Background Bifidobacteria represent an important gut commensal in humans, particularly during initial microbiome assembly in the first year of life. Enrichment of Bifidobacterium is mediated though the utilization of human milk oligosaccharides (HMOs), as several human-adapted species have dedicated genomic loci for transport and metabolism of these glycans. This results in the release of fermentation products into the gut lumen which may offer physiological benefits to the host. Synbiotic pairing of probiotic species with a cognate prebiotic delivers a competitive advantage, as the prebiotic provides a nutrient niche. Methods To determine the fitness advantage and metabolic characteristics of an HMO-catabolizing Bifidobacterium strain in the presence or absence of 2′-fucosyllactose (2′-FL), conventionally colonized mice were gavaged with either Bifidobacterium pseudocatenulatum MP80 (B.p. MP80) (as the probiotic) or saline during the first 3 days of the experiment and received water or water containing 2′-FL (as the prebiotic) throughout the study. Results 16S rRNA gene sequencing revealed that mice provided only B.p. MP80 were observed to have a similar microbiota composition as control mice throughout the experiment with a consistently low proportion of Bifidobacteriaceae present. Using 1H NMR spectroscopy, similar metabolic profiles of gut luminal contents and serum were observed between the control and B.p. MP80 group. Conversely, synbiotic supplemented mice exhibited dramatic shifts in their community structure across time with an overall increased, yet variable, proportion of Bifidobacteriaceae following oral inoculation. Parsing the synbiotic group into high and moderate bifidobacterial persistence based on the median proportion of Bifidobacteriaceae, significant differences in gut microbial diversity and metabolite profiles were observed. Notably, metabolites associated with the fermentation of 2′-FL by bifidobacteria were significantly greater in mice with a high proportion of Bifidobacteriaceae in the gut suggesting metabolite production scales with population density. Moreover, 1,2-propanediol, a fucose fermentation product, was only observed in the liver and brain of mice harboring high proportions of Bifidobacteriaceae. Conclusions This study reinforces that the colonization of the gut with a commensal microorganism does not guarantee a specific functional output. Video Abstract